Diffusion of Educational Innovation Decision Making in Pesantren - Idam Mustofa; Athok Fu’adi (P3M IAI Nusantara Batang Hari, 2023)
Political policy is needed so that the government can regulate its interests so that education policy is a form of educational politics. In this regard, educational institutions that wish to exist within the framework of the national education system have a preference for carrying out government policies. This is a challenge for the world of Islamic boarding schools that wish to apply Islamic religious education, both formal and informal. The challenge of pesantren lies in the efforts to diffuse educational innovations in the political context of education. The study reviewed in this article is a literature review that seeks to present the idea of diffusion of educational innovation decision-making in Islamic boarding schools by using Everett M. Rogers' innovation diffusion perspective within the decision-making framework of James L. Gibson and George R. Terry's management functions. The results of the study show that the diffusion of innovation as formulated by Rogers is a process of communication within a social system using certain means and time which leads to the adoption process. To ensure the involvement of all elements of education, from policymakers to local units, diffusion must be based on decentralization. In addition, the local unit becomes a determinant in making decisions on the implementation of management functions. Local unit - in the context of management the staff involved in decision-making at the planning stage will be bound by the consequences of an innovation (desirable consequence). Innovations can be carried out by pesantren administrators at the direct consequence stage.